New Phenylethanoid Glycosides from Cistanche phelypaea and Their Activity as Inhibitors of Monoacylglycerol Lipase (MAGL) - Beladjila, Khadidja Aya; Berrehal, Djemaa; De Tommasi, Nunziatina; Granchi, Carlotta; Bononi, Giulia; Braca, Alessandra; De Leo, Marinella (Planta Medica, 2018)
Four new phenylethanoid glycosides (1–4), 1-β-p-hydroxyphenyl-ethyl-2-O-acetyl-3,6-di-α-l-rhamnopyranosyl-β-d-glucopyranoside (1), 1-β-p-hydroxyphenyl-ethyl-3,6-O-di-α-l-rhamnopyranosyl-β-d-glucopyranoside (2), 1-β-p-hydroxyphenyl-ethyl-2-O-acetyl-3,6-di-α-l-rhamnopyranosyl-4-p-coumaroyl-β-d-glucopyranoside (3), and 1-β-p-hydroxyphenyl-ethyl-3,6-di-α-l-rhamnopyranosyl-4-p-coumaroyl-β-d-glucopyranoside (4), together with three known compounds, were isolated from the n-butanol extract of Cistanche phelypaea aerial parts. The structural characterization of all compounds was performed by spectroscopic analyses, including 1D and 2D NMR, and HRESIMS experiments. The isolated compounds were assayed for their inhibitory activity on two enzymes involved in the peculiar glycolytic or lipidic metabolism of cancer cells, human lactate dehydrogenase (LDH), and monoacylglycerol lipase (MAGL), respectively. All the compounds showed negligible activity on LDH, whereas some of them displayed a certain inhibition activity on MAGL. In particular, compound 1 was the most active on MAGL, showing an IC50 value of 88.0 µM, and modeling studies rationalized the supposed binding mode of 1 in the MAGL active site.
Keywords: Cistanche phelypaea; Orobanchaceae; phenylethanoid glycosides; cancer; monoacylglycerol lipase; lactate dehydrogenase